LITERASI DIGITAL SEBAGAI UPAYA PENANGANAN CULTURE SHOCK PASCA PANDEMI COVID-19 - Alamsyah, Femi Fauziah (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2022)
The COVID-19 pandemic has forced all people to adapt to all digital-based activities. However, this is not something easy, people are vulnerable to symptoms of Culture Shock or it can also be called cultural shock, where a person experiences feelings of psychic and physical discomfort when in a new environment and atmosphere. The purpose of this study is to find out how the symptoms of Culture Shock experienced by the Babakan Salam community, what are their efforts to adapt to digital culture, and how the forms of digital literacy are as an effort to deal with culture shock symptoms in the Babakan Salam village community. The research method used descriptive qualitative, describing the phenomena that occur in the object of study, does not perform comparisons and hypothesis tests on the object being researched. The theory used in this study is the Culture Shock Theory by Kalvero Oberg, where Oberg said there are 4 stages in Culture Shock, namely Excitement Phase, Culture Shock, Adjustment Phase, Mastery Phase, which is depicted in a curve or commonly called U-curve Hyptosess. The results of the study explained that there were two groups that experienced symptoms of Culture Shock, namely the Student group and the Parents group. Both go through four stages or phases of Culture Shock. One of the efforts they make to be able to adapt to all-digital habits is Digital Literacy, as for the form of digital literacy in the form of independent initiative activities and service activities from the local government. Basically, the Babakan Salam Community has been able to adapt to cultural changes after the Covid-19 pandemic, although the understanding of digital literacy is said to be not optimal and comprehensive.